Postoperative radiotherapy in subtotally resected recurrent WHO grade 1 meningiomas with intermediate-/high-risk molecular profiles - Deng, Maximilian; Maas, Sybren L. N.; Anil, Günes; Sievers, Philipp; Lischalk, Jonathan W; Zhao, Eric Yanfei; Rauh, Sophie; Jessen, Inga; Eichkorn, Tanja; Regnery, Sebastian; Bauer, Lukas; Held, Thomas; et al. (Neuro-Oncology, 2025)
Meningiomas represent the most common primary intracranial tumors in adults, with World Health Organization (WHO) grade 1 typically associated with favorable outcomes following gross total resection (GTR).This retrospective study included patients with CNS WHO grade 1 meningioma and available DNA methylation profiles (n = 210). Clinical tumor characteristics and treatment course (eg, surgical resection, extent of resection, radiotherapy [RT]) were evaluated. Integrated Scores (InS) were calculated based on methylation family using the DKFZ brain tumor classifier, CNS WHO grading, and chromosomal losses, categorized as low, intermediate, or high. Survival analyses employed Kaplan-Meier and Cox regression methods, with local PFS defined as the primary endpoint.In newly diagnosed cases, GTR was associated with a 93.0% 3-year progression-free survival (PFS), compared to 69.3% following subtotal resection (STR). Stratification by IntS showed that patients in the IntS-low group had superior outcomes: 3-year PFS of 93.4 after GTR and 77.4% after STR. In contrast, patients with IntS-intermediate/high profiles showed significantly worse outcomes, with PFS of 85.9% after GTR and 40.0% after STR. Following tumor recurrence, particularly those with IntS-intermediate/high, postoperative RT after STR may improve 3-year PFS to 88.9%, compared to much lower PFS rates in newly diagnosed cases managed without adjuvant RT after STR (3-year PFS: 40.0%).Our findings highlight the combined impact of both the extent of resection and molecular risk profile on prognosis in newly diagnosed cases. While conservative management is feasible in lower-risk primary cases, recurrent or higher-risk patients may benefit from early postoperative RT.